Principles of supply chain management a balanced approach - Wisner, Joel D.; Tan, Keah-Choon; Leong, G. Keong (Cengage, 2023)
This unique text discusses supply management from four perspectives: purchasing, operations, logistics and process integration. This balanced approach varies significantly from other books that concentrate on only one area. Updates and new references highlight recent events, including supply chain challenges during the global pandemic. This edition follows the natural flow through the supply chain of trading partners as you examine how supply chain management impacts all areas and processes of the firm. You learn to address real concerns in both domestic and global supply chains as well-organized chapters demonstrate the practical applications of supply chain management in today's workplace. Updated profiles and interesting business examples demonstrate practices at work. MindTap digital resources are available to assist in mastering concepts.